Representation, activism, health promotion, and communication: The role of art in advancing global health and social justice. - Mark Donald C Reñosa; Kelly E Perry; Siddharth Srivastava; Angeli Rawat; Zaida Orth; Phuong Bich Tran; Diane Woei-Quan Chong; Joseph Kazibwe; Maira Shaukat; Germán Andrés Alarcón Garavito; Mazen Boroudi; Vivek Dsouza; et al. (PLOS Global Public Health)
This viewpoint advocates for the inclusion of art in global health discourse and practice. We explore four areas in which art can be leveraged to improve global health: (1) to amplify disenfranchised voices, (2) to advance social justice activism, (3) to strengthen communities and individuals, and (4) to improve global health communication. Drawing on community-driven art initiatives, we argue for an inclusive approach that respects diverse cultural perspectives and uplifts marginalized voices. Emphasizing interdisciplinary collaboration and ethical engagement, our framework invites global health discourse and practice to integrate art in order to foster empathy, challenge systemic inequities, and envision sustainable futures. By centering art, we seek to enrich the global health discipline with insights and transformative potential grounded in human experiences, cultural diversity, and shared humanity.